Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To find and simplify [tex]\(\left(\frac{f}{g}\right)(-2)\)[/tex] given the functions:
[tex]\[ f(x) = x(-2x - 3) \][/tex]
and
[tex]\[ g(x) = -2x - 3 \][/tex]
we need to follow these steps:
1. Compute [tex]\( f(-2) \)[/tex]:
[tex]\[ f(x) = x(-2x - 3) \][/tex]
Substitute [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = (-2)(-2(-2) - 3) \][/tex]
Simplify inside the parentheses:
[tex]\[ -2(-2(-2) - 3) = -2(4 - 3) = -2 \cdot 1 \][/tex]
So,
[tex]\[ f(-2) = -2 \][/tex]
2. Compute [tex]\( g(-2) \)[/tex]:
[tex]\[ g(x) = -2x - 3 \][/tex]
Substitute [tex]\( x = -2 \)[/tex]:
[tex]\[ g(-2) = -2(-2) - 3 \][/tex]
Simplify the expression:
[tex]\[ -2(-2) - 3 = 4 - 3 = 1 \][/tex]
So,
[tex]\[ g(-2) = 1 \][/tex]
3. Compute [tex]\(\left(\frac{f}{g}\right)(-2)\)[/tex]:
[tex]\[ \left(\frac{f}{g}\right)(-2) = \frac{f(-2)}{g(-2)} \][/tex]
We already have:
[tex]\[ f(-2) = -2 \][/tex]
[tex]\[ g(-2) = 1 \][/tex]
So,
[tex]\[ \left(\frac{f}{g}\right)(-2) = \frac{-2}{1} = -2 \][/tex]
Therefore, [tex]\(\left(\frac{f}{g}\right)(-2)\)[/tex] is [tex]\(-2\)[/tex].
[tex]\[ f(x) = x(-2x - 3) \][/tex]
and
[tex]\[ g(x) = -2x - 3 \][/tex]
we need to follow these steps:
1. Compute [tex]\( f(-2) \)[/tex]:
[tex]\[ f(x) = x(-2x - 3) \][/tex]
Substitute [tex]\( x = -2 \)[/tex]:
[tex]\[ f(-2) = (-2)(-2(-2) - 3) \][/tex]
Simplify inside the parentheses:
[tex]\[ -2(-2(-2) - 3) = -2(4 - 3) = -2 \cdot 1 \][/tex]
So,
[tex]\[ f(-2) = -2 \][/tex]
2. Compute [tex]\( g(-2) \)[/tex]:
[tex]\[ g(x) = -2x - 3 \][/tex]
Substitute [tex]\( x = -2 \)[/tex]:
[tex]\[ g(-2) = -2(-2) - 3 \][/tex]
Simplify the expression:
[tex]\[ -2(-2) - 3 = 4 - 3 = 1 \][/tex]
So,
[tex]\[ g(-2) = 1 \][/tex]
3. Compute [tex]\(\left(\frac{f}{g}\right)(-2)\)[/tex]:
[tex]\[ \left(\frac{f}{g}\right)(-2) = \frac{f(-2)}{g(-2)} \][/tex]
We already have:
[tex]\[ f(-2) = -2 \][/tex]
[tex]\[ g(-2) = 1 \][/tex]
So,
[tex]\[ \left(\frac{f}{g}\right)(-2) = \frac{-2}{1} = -2 \][/tex]
Therefore, [tex]\(\left(\frac{f}{g}\right)(-2)\)[/tex] is [tex]\(-2\)[/tex].
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.